Color atlas of histology - Gartner, Leslie P., 1943-; Hiatt, James L., 1934- (Philadelphia : Lippincott Williams & Wilkins, 2006)
"This compact atlas provides medical, dental, allied health, and biology students with an outstanding collection of histology images for all of the major tissue classes and body systems. The Fourth Edition features a completely re-digitized image collection, along with other hallmarks of this atlas that have been proven over time, including its concise writing style, compact size/format, and quick introduction/background for each chapter that reviews essential concepts, histophysiology, and clinical considerations."
The cell -- Epithelium and glands -- Connective tissue -- Cartilage and bone -- Blood and hemopoiesis -- Muscle -- Nervous tissue -- Circulatory system -- Lymphoid tissue -- Endocrine system -- Integument -- Respiratory system -- Digestive system I: oral region -- Digestive system II: alimentary canal -- Digestive system III: digestive glands -- Urinary system -- Female reproductive system -- Male reproductive system -- Special senses
System requirements for accompanying CD-ROM: Windows: Windows 2000, Windows NT 4.0, or Windows XP, Pentium II, Internet Explorer 5.5 or higher or Netscape 7.02; Macintosh: Apple Power Macintosh or compatible computer, MAC OS version 9.2 or later
Keywords: Histology -- Atlases; Histology -- Atlases